Cross-education of skill: assessment of overhand throwing using product- and process-oriented assessment - Dapi, G.; Cleather, D. J.; Murray, M. (Research Quarterly for Exercise and Sport, 2024)
Purpose The aims of the present study were to: (1) investigate the magnitude and direction of the cross-education effect in a unilateral sport skill (overhand throw) and (2) to establish which practice condition (dominant hand only or alternating hands) would yield the best results.